The Influence of Corporate Social Responsibility on Earning Response Coefficient with Good Corporate Governance as a Moderating Variable - Putri, Dewi Raditya Mutyarini; H. Bambang Suprasto (E-Jurnal Akuntansi, 2026)
The purpose of this study was to determine the effect of corporate social responsibility on earnings response coefficient with good corporate governance as a moderating variable. The population used in this study are all companies listed on the Indonesia Stock Exchange in the 2015-2017 period. The analysis technique used is Moderated Regression Analysis (MRA) using the Statistical Product and Service Solution (SPSS) program. The results show that the knowledge of Corporate Social Responsibility (X), Good Corporate Governance (Z), and interaction variables between Corporate Social Responsibility and Good Corporate Governance (XZ) simultaneously affect Earning Response Coefficient which is able to empirically prove the theory used in research this is signal theory, legitimacy theory and contingency theory. The theoretical implications of the results of this study can also provide additional references for further research that discusses Corporate Social Responsibility, Good Corporate Governance and Earning Response Coefficient.